Le chevalier et le prêtre Axiologies dans les chansons de la croisade - Abramowicz, Maciej (Romanica Silesiana)
In keeping with the epic conception of reality, the Crusade songs La Chanson d’Antioche and La Conquête de Jérusalem realize the axiological opposition between Good and Evil, embodied in the armies of the Crusaders and the Muslims. However, the appearance of two value systems within one work neutralizes the oppositions, with many of the actions losing their transgressive character. This capacity for neutralization belongs solely to the literary discourse, whereas in medieval realities axiological systems were far from elastic. A distinctive element of the world of the Christians in these texts is the army of King Tafur, which breaks all chivalric rules, hardly a case of transgression this, but rather an incentive for praise and respect. The king’s army constitutes an interesting example of the transference of the warriors’ desires, restricted as they are by the chivalric code. Key words: Crusade, epic, axiology, religion knighthood.